SIFAT DAN KEPRIBADIAN GURU PERSPEKTIF AL-QUR’AN SURAT AL-MUDASSIR AYAT 1-7 - Ubaidillah, Mohammad Farah (Fakultas Agama Islam Universitas Islam Madura, 2018)
The teacher is a noble profession. He has a role as a substitute for parents in Islam. The teacher is the successor to the struggle of the prophets. This noble position requires the nature of a personality that can be modeled by his students. This article contains a post about the nature and personality of the perspective of al-Qur'an teacher based on Al-Mudassir 1-7 Verses. This letter came down as an order to the prophet Muhammad to preach (educate) the people of Mecca at that time through the science of education, in the Surah Al-Mudassir 1-7 verses, there are six traits and personalities that must be possessed by a teacher to succeedsin carrying out his duties as an educator.